The Environmental Consequences Concerning the Use of Timber in the Built Environment - Hill, Callum Aidan Stephen (Frontiers in Built Environment, 2019)
The use of timber in the built environment provides environmental benefits which arise dues to the substitution of higher impact materials, the storage of sequestered atmospheric carbon in long-life products and the recovery of inherent energy in the material at the end of life. This manuscript explores the issues that determine how embodied energy and global warming potential are calculated and reported. The article discusses the literature which compares the use of timber in the built environment and other materials in life cycle assessment studies. The issue of how sequestered carbon should be dealt with is also discussed. End of life considerations are also addressed.